Breeding possibilities of Booroola Merino in East-Europe - Veress, L.; Horek, F.; Komlosi, T. (Agricultural and Food Science, 1988)
Booroola Merino (BM)rams and ewes were imported from New Zealand to Hungary and Czechoslovakia in the 1980’s. Part of the imported animals were proved to be homozygous for the F gene. Frozen semen of these has been used for spreading this gene to Hungarian (HM) and Czechish (CM) Merinos. The crossbred lambs were 4—7 % lighter at birth and at 30 d.,6—24 % lighter at 100 d. and 5—10 % lighter at 1-yr than HM. The 1-yr weight was 10—22 % lighter than that of CM. Greasy fleece weights were 5—10 % higher, staple lengths 7—11 % longer than in HM or CM, while fibres were finer. The litter size of BM x HM ewes at 1 st lambing was 1.42, at 2nd 1.52 and at 3rd 1.69, while the last figure for HM ewes was 1.15. The % of twins born to the BM x HM ewes was ca. 35 %, when HM ewes had 12%. The corresponding figures for triplets were 9 and 0.2 %. The BM x HM crosses had shorter anestrus periods after lambing than HM ewes, except after the first lambing. The BM x HM ewes produced 2.4 lambs/yr. in a continuous lambing system, while HM ewes gave 1.9 lambs.